Leadership dalam Perspektif Islam - A'ang Yusril Musyafa; Binti Maunah (Tarbawi: Journal of Islamic Education, 2022)
Leadership is someone who can influence, encourage, invite, guide, move others to accept the influence of something that can help achieve goals certain. Leadership is essentially related to human power or groups that organized, and as a force or potential. One of those guidelines is a human obligation to obey everything that is ordered for a better life and stay away from all prohibitions to keep away from bad deeds. In the course of the dynamics of human life, it turns out that Humans cannot live alone, humans need a leader. The purpose of this research is to analyze how the concept of leadership in Islam, understand what leadership is, leadership in Islam, and what is the urgency of a leader in educational institutions. This research using the library research method, in analyzing the model data this method using a descriptive analysis model. As a source of information, namely; scientific books, reports research, scientific papers and journals. From the results of this study, it can be explained that The concept of leadership in Islam is a point of view that forms the basis of thought in being a leader. The concepts possessed by Islamic teachings in looking at leadership, leadership in Islam includes several aspects, namely; aspect influence, spiritual aspect, and characteristic aspect.